ANALISIS STUDI KELAYAKAN BISNIS SYARIAH PADA USAHA KULINER RISOL MAYO - Aulia Ma'rifah; Muhammad Rizky Ibnu Azis; Suryadi Alamsyah; Mega Oktaviany (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
Risol mayo is one type of food that is popular and has promising market potential. In developing a culinary business such as risol mayo, it is necessary to conduct a business feasibility study process. A feasibility study is an activity carried out to analyze in depth the business activities to be carried out. This study aims to analyze the feasibility of risol mayo business in financial, technical, market, and social aspects. The research method used is qualitative descriptive data analysis. The interview method was conducted to gain an in-depth understanding of the risol mayo market. In addition, related literature studies were also conducted to obtain relevant information about the market. The results of this study are expected to be an evaluation material to improve and develop the risol mayo culinary business, as well as make a positive contribution to the culinary industry in Indonesia.Keywords: Risol Mayo, Business Feasibility Analysis and Aspects of Assessment